Development of a new nanocomposite based on reduced graphene oxide modified anatase “black TiO2” nanostructures with exposed {001} facets towards photocatalytic degradation of Endocrine Disrupting Chemicals (EDCs) under natural Sunlight irradiation. - Nalandhiran; Pugazhenthiran (2023)
RESULTS OBTAINED: For each specific goal, describe or summarize the results obtained. Relate each one to work already published and/or manuscripts submitted. In the Annex section include additional information deemed pertinent and relevant to the evaluation process. The maximum length for this section is 5 pages. (Arial or Verdana, font size 10). Endocrine disrupting chemicals (EDCs) in particular medicines, pesticides, detergents and industrial chemicals at very small (ng/L) concentration cause serious health and environmental effects. Further, millions of people including children lose their life annually due to water-borne diseases caused by the consumption of contaminated fresh water. Fresh-water resources are predominantly polluted by effluents discharged from various industries that are toxic to aquatic environment and human beings. In addition, the accumulation of various synthetic organic compounds such as dyes, phenols, organochlorides, antibiotics and etc., are known to cause great harm to human health (carcinogenic, teratogenic and mutagenic) even when their concentration in water is less than nano-micro molar magnitude. Hence, problems related to water are expected to grow worse in the coming decades with freshwater scarcity occurring globally even in the regions currently endowed with freshwater rich. Addressing these serious problems requires robust advanced technologies for purifying water polluted with synthetic organic compounds wastes in an economical way and with less energy consumption. Unfortunately, conventional wastewater treatment systems are limited to complete removal of EDCs. In view of the above facts, the current research work was focused the state-of-the-art research activities and latest advancements in the design of different nano-structured materials via various strategies, including hydrothermal/solvothermal, solid phase methods and etc. To overcome the large band gap of nano-structured semiconductor materials and rapid recombination of photo generated charge carriers, ...